Monocyte-derived Galectin-9 and PD-L1 differentially impair adaptive and innate immune response in chronic HBV infection and their expression remain unaltered after antiviral therapy - Dey, Debangana; Biswas, Satabdi; Pal, Sourina; Nandi, Sarthak; Khatun, Najma; Jha, Rambha; Chakraborty, Bidhan Chandra; Baidya, Ayana; Ghosh, Ranajoy; Banerjee, Soma; Ahammed, SK Mahiuddin; Chowdhury, Abhijit; et al. (Frontiers in Immunology, 2024)
Introduction: Patients with chronic HBV infection (CHI) exhibit defective anti-viral immune-response whose underlying causes still remain unclear. Monocytes act as immune sentinels for pathogens and can regulate immunity via interaction with other immune-cells, apart from differentiating into macrophages. Immune-checkpoint molecules (ICMs) expressed by immune-cells, including monocytes are known to negatively regulate immune-responses. Here, we evaluated the expression of ICMs, namely, Gal-9, PD-L1, and CTLA-4 on monocytes in different phases of CHI, identified the viral and the host factors causing their aberrant expression and investigated their impact during interaction of monocytes with T-cells, B-cells and NK-cells and also on monocyte to macrophage differentiation. Influence of Tenofovir therapy on the expression of monocytic ICMs was also studied. Methods: Collection of blood and liver-tissue samples from HBV infected patients and controls, flow-cytometry, cell sorting, cell culture and immune-fluorescence were performed for this study. Results: Gal-9+ and PD-L1+-monocytes were significantly increased in HBeAg-positive as well as HBeAg-negative chronic hepatitis B (CHB) patients than healthy controls (HC). In immune-tolerant (IT) subjects, only Gal-9+-monocytes and in inactive carriers (IC), PD-L1+-monocytes were higher than HC while CTLA-4+-monocytes remained comparable among groups. High serum Hepatitis B surface antigen (HBsAg) concentration in CHB as well as IT and TNF-α in CHB triggered monocytic Gal-9-expression whereas, PD-L1 was induced by elevated TNF-α and IL-4 in CHB and IL-1β in CHB and IC. Purified monocytes from CHB and IT having high Gal-9 expression led to expansion of CD4+CD25+FOXP3+-Tregs, CD19+IL-10+-Bregs and CD19+CD27-CD21--atypical memory B-cells and these monocytes also preferentially differentiated into M2-macrophages. These phenomena were reversed by anti-Gal-9-antibody. Parallelly, PD-L1+-monocytes in CHB and IC reduced IL-2/IFN-γ and IL-6 production by HBV-specific T- and B-cells respectively, which were restored by anti-PD-L1-antibody. Both Gal-9+- and PD-L1+-monocytes caused decline in IFN-γ+-NK-cells but enhanced IL-10-expressing HBV-specific-T-cells and NK-cells. Increased intrahepatic CD14+Gal-9+ and CD14+PD-L1+-monocytes were noted in CHB patients than HC. One-year tenofovir therapy failed to reduce monocytic Gal-9 and PD-L1 along with the levels of HBsAg, TNF-α, IL-1β and IL-4. Conclusions: Monocytic Gal-9 and PD-L1, expressed heterogeneously in different phases of CHI, exert diverse inhibitory effects on immune-responses and their therapeutic targeting could boost anti-HBV immunity.